2015
DOI: 10.3233/bmr-150618
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between isometric trunk muscle endurance and physical activity related energy expenditure in healthy young adults

Abstract: According to our findings, trunk muscle endurance is not related to physical activity related energy expenditure in healthy young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Similarly, no gender differences existed in lumbar extensor muscle endurance and thoracolumbar curvatures in our study results that involved young adults. These results are in agreement with the results of an earlier study reporting lumbar extensor muscle endurance among young males and females (Bayraktar et al 2015). To the best of the authors' knowledge, there are no previous studies reporting thoracolumbar curvatures among healthy young adults.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, no gender differences existed in lumbar extensor muscle endurance and thoracolumbar curvatures in our study results that involved young adults. These results are in agreement with the results of an earlier study reporting lumbar extensor muscle endurance among young males and females (Bayraktar et al 2015). To the best of the authors' knowledge, there are no previous studies reporting thoracolumbar curvatures among healthy young adults.…”
Section: Discussionsupporting
confidence: 92%
“…8,10,14 In patients with AS, atrophy has been shown to occur because of 25 In our study, the median values obtained by the participants in core endurance tests are very similar to those obtained by Acar et al 16 When the results from other studies that were conducted in different healthy populations were compared with our results, it was observed that the CME times of the AS patients in the present study were significantly lower than that of healthy population with similar ages. 16,24,26 Although fatigue is one of the main symptoms of AS, it has been vastly ignored for a long period. Approximately, 53% to 65% of individuals with AS experience chronic fatigue due to the physical and psychological factors and chronic inflammatory process of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that results of the muscular balance are important, therefore judging according to the ratios, seems a more reliable method to decide a good core stability status 25 . The side bridge test assesses primarily the lateral core muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Juker, McGILL, Kropf, Steffen 26 investigated this test with myoelectric equipment and reported it as the most effective way to assess and train the abdominal obliques with little psoas activity. The side bridge test has high intrarater reliability and has been suggested in the literature as an appropriate method to test lateral trunk muscle endurance in clinical environments 25 .…”
Section: Discussionmentioning
confidence: 99%